Enteropathy and gut dysbiosis as obstacles to achieve immune recovery in undetectable people with HIV: a clinical view of evidence, successes, and projections. (1st March 2023) - Castillo-Rozas, Gabriel; Lopez, Mercedes N.; Soto-Rifo, Ricardo; Vidal, Roberto; Cortes, Claudia P.
Abstract : Immune performance following antiretroviral therapy initiation varies among patients. Despite achieving viral undetectability, a subgroup of patients fails to restore CD4 + T-cell counts during follow-up, which exposes them to non-AIDS defining comorbidities and increased mortality. Unfortunately, its mechanisms are incompletely understood, and no specific treatment is available. In this review, we address some of the pathophysiological aspects of the poor immune response from a translational perspective, with emphasis in the interaction between gut microbiome, intestinal epithelial dysfunction, and immune system, and we also discuss some studies attempting to improve immune performance by intervening in this vicious cycle.